2016
DOI: 10.1002/jnr.23996
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity treadmill running impairs cognitive behavior and hippocampal synaptic plasticity of rats via activation of inflammatory response

Abstract: Although appropriate exercise is beneficial for enhancing brain functions, high-intensity exercise (HIE)-induced cognitive dysfunction is causing more and more concerns nowadays. In the present study, we observed the effects of high-intensity treadmill running on the spatial learning of the adult Sprague Dawley male rats in Y-maze (n = 16 per group), and investigated its possible electrophysiological and molecular mechanisms by examining in vivo hippocampal long-term potentiation (LTP), central inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 38 publications
3
15
1
Order By: Relevance
“…And the activation of microglia in the hippocampus can lead to an increase in the production of inflammatory cytokines such as TNF-α, IL-1β, ROS and NO [51]. Similar to our findings, Sun et al reported that high-intensity treadmill exercise (V = 20 m/min, duration of fatigue/day for 7 days) activated astrocytes and microglia and increased expression of TNF-α and IL-1β in the hippocampus of rats which led to cognitive impairment [22]. Furthermore, some studies have shown that CRP has a predisposing role in dementia and cognitive impairment, and that high levels of CRP might cause AD [5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…And the activation of microglia in the hippocampus can lead to an increase in the production of inflammatory cytokines such as TNF-α, IL-1β, ROS and NO [51]. Similar to our findings, Sun et al reported that high-intensity treadmill exercise (V = 20 m/min, duration of fatigue/day for 7 days) activated astrocytes and microglia and increased expression of TNF-α and IL-1β in the hippocampus of rats which led to cognitive impairment [22]. Furthermore, some studies have shown that CRP has a predisposing role in dementia and cognitive impairment, and that high levels of CRP might cause AD [5].…”
Section: Discussionsupporting
confidence: 90%
“…Overload exercise without adequate rest (overtraining) will lead to tissue injury, especially in muscle and joints, and release of trauma-related cytokines, which activate circulating monocytes to produce inflammatory cytokines [21]. It has been demonstrated that high-intensity exercise increases the levels of TNF-α, IL-1β, IL-6 and CRP [22,23]. Also, some studies have shown that acute exercise and overtraining lead to the production of reactive oxygen and nitrogen species and oxidative stress, while regular exercise can stimulate the antioxidant system and protect against the side effects of oxidative damage [24].…”
Section: Introductionmentioning
confidence: 99%
“…Thomson et al ( 2009 ) found that athletes’ decision-making time decreased and decision-making errors increased after EF. Sun et al ( 2017 ) showed that high-intensity treadmill running impaired the mice’ spatial memory and hippocampal synaptic plasticity. Corticostriatal synaptic plasticity plays a crucial role in modulating motor activity, and is the cellular basis of motor skill learning and cognitive performance (Calabresi et al, 1996 ; Mahon et al, 2004 ; Chepkova et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our proteomic array screen did not detect any significant change of JNK phosphorylation in the hippocampal lysates following voluntary wheel running in the current study. We speculate that this difference may be attributed to the varied paradigms applied, given that some prior studies have found that resistance training did not affect cortical or hippocampal JNK levels, whereas high-intensity treadmill running elevated the phosphorylation of JNK (Sun et al, 2017;Henrique et al, 2018).…”
Section: Discussionmentioning
confidence: 90%